Explicações teleológicas no ensino de evolução: um estudo sobre os saberes mobilizados por professores de Biologia - Azevedo, Maicon Jeferson da Costa (2008)
This work aims to investigate the teleological thought in its implications for the education and training of biology teachers. In particular, the research seeks to understand the extent to which teachers use the teleological arguments while explaining topics of evolution. Methodology: The empirical work focuses on the solutions presented by teachers to the various instances and different uses of the teleological thought in classroom. The theoretical basis of the study articulates the philosophical sense that the teleology historically takes in the Biological Sciences with the specific form of knowledge that circulates in the school, the school knowledge. The analytical basis of the research is supported by Jean-Claude Forquin s contributions when he assumes that the changes by which the scientific knowledge suffers in the formation of the school knowledge, make the school special place for the production of knowledge and practices. Also, the analysis has made use of Maurice Tardif s contributions to understand the teleological explanations in school as an expression of the teachers knowledge. Content: The research has looked for the philosophical definitions of the teleological arguments and teleological explanations in didactic perspectives. The association of teleology with science has deep roots, going back to Aristotelian thought. In the Biological Sciences or even in Darwin s work it has not been possible to withdraw completely the teleological thought and there are numerous reports of themes that deal with this issue. The teleological thought is also rooted in the Science teaching, demanding further studies and reflections. Conclusion: The research has showed that teachers s view is closer to a common sense definition for the term evolution and the evolutionary theories, suggesting a linear and progressive view. It was also noticed that the evolutionary process is seen as a consequence from progressive action. revealing a close relationship between teleology and progress. The teleological thought was present in the speeches of Biology teachers through various arguments justified by them as a way to facilitate students understanding. Based on the analysis, we suggest that it can be unproductive to withdrawal the teleological thought from teaching biology in schools, given the advantages that this didactic reading of biological phenomena can offer. We recommend that it is necessary, though, to use the teleological explanation with caution and only in specific situations.